GE_GERICHTE C/998/2014 vom 12. Mai 2017 - GE Cour de justice (2017)
DIVORCE ; DROIT DE GARDE ; RELATIONS PERSONNELLES ; OBLIGATION D'ENTRETIEN ; ENFANT ; LIQUIDATION DU RÉGIME MATRIMONIAL ; COPROPRIÉTÉ | CC.206; CC.209; CC.273; CC.285;